Profil Kebutuhan dan Pemetaan Pemahaman Pelaku Pendidikan SMAN 3 Sidoarjo terhadap Asesmen Kompetensi Minimum - Rokhim, Deni Ainur; Agustina, Nur Indah; Asrori, Muhammad Roy; Putra, Moch. Chesa Nur Hidayat Arif; Habiddin, Habiddin; Peni, Ristiwi; Wahyudi, Bambang; Wahyudi, Asnan (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Minimum Competency Assessment (AKM) is an assessment of the essential competencies needed by all students to develop their capacity and participate positively in society. The AKM component consists of literacy and numeracy. This study aims to determine the needs and understanding of education actors at SMAN 3 Sidoarjo towards AKM. The research method used is a qualitative survey method. The data collection process was carried out by distributing research questionnaires to 30 students and 25 teachers at SMAN 3 Sidoarjo. The results showed that AKM is very important and needed by both teachers and students because AKM can improve teacher and student competencies, both literacy and numeracy competencies. Teachers’ and students’ understanding of AKM showed a general level of understanding without any misconceptions. Therefore, teachers and students make careful preparations in dealing with AKM.